Características en la transición laboral de miembros en situación de retiro de una de las fuerzas armadas del Perú - De La Flor Pittaluga, Camila (2020)
This qualitative research project is exploratory and phenemenological in nature. Its objective is to explore the main characteristics that are present in the labor transition of a group of Peruvian naval. t record. The population was 12 Peruvian Naval who were invited to retreat from the ranks of Frigate Captain to Vice Admiral. The information was collected through the semi-structured interview. The main findings indicate that the transition of the seafarer to the civilian work environment is characterized by an increase in their income and a better relationship with their families. Likewise, the high adaptability, networking or network of contacts and the skills acquired in their training are pointed out as elements that favor their transition. As elements that hinder their transition, ignorance of the market and resistance to adequately accept the withdrawal of the Institution were identified